Organic Thin Film Transistor with Carbon Nanotube Electrodes - Kianoosh Safari; Ali Rafiee; Hamidreza Dalili Oskouei (Bulletin of Electrical Engineering and Informatics, 2016)
The contact resistance between organic semiconductors and metallic electrodesaffectsthe performance of the organic thin film transistor (OTFT) negatively so that it may make thefield effect mobility of charge carrier seem small. In order to reduce the contact resistance weused conducting Carbon Nanotube (CNT) films, which consist of the same element as the basicmaterial of the organic semiconductors, as source or drain electrodes. The measurements oftransistor properties based on pentacene single crystals have been carried out by using both CNTfilm electrodes and metal electrodes